E-thesis management system - Nursyazwa, Sadri (2011)
E-Thesis Management System (ETMS) is proposed to provide an efficient management system for PSM/PTA thesis in faculty's collection.The objective of ETMS is to provide the prototype of searching the thesis for student in order to find the suitable title of PSM/PTA project from previous semester.it also provides information and availability of the thesis by transforming the process into the computerize system:.The system's interface design is developed using Adobe Dreamweaver CS4,and will used Spiral Life Cycle Model as the methodology. MySQL is used to construct the database and store the thesis information. This system is a web based application and to be used by Student,lecturer and Coordinator. The system's performance is expected to be better than the conventional system because it manages the thesis easier and faster.This project it will contribute towards a better thesis management in future. It also :aims to overcome the problem of missing thesis's data as well as the fast retrieval of thesis information.